Tunability and enhancement of mechanical behavior with additively manufactured bio-inspired hierarchical suture interfaces. Issue 17 (24th July 2014) - Lin, Erica; Li, Yaning; Weaver, James C.; Ortiz, Christine; Boyce, Mary C.
Abstract